2018
DOI: 10.4085/1302120
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Factors Perceived to Influence Development of Diagnostic Reasoning in Athletic Trainers and Athletic Training Students

Abstract: Context: Diagnostic reasoning is acknowledged as a vital skill for medical practice, but research regarding this core aspect of medical cognition as it pertains to athletic training contexts is scarce. To compare athletic training-specific clinical reasoning skills with those of other health care practitioners, educators need to better understand how athletic trainers (ATs) think, what helps them think better, and what may hinder their thinking skills as related to diagnostic reasoning challenges in the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…[53][54][55][56][57] Further, both students and faculty believe that diverse clinical experiences and mentorship from practicing clinicians contribute to newly credentialed ATs feeling prepared to practice independently. 58,59 Given the perception from both educators and students of the learning potential in clinical education, it seems prudent to conduct the majority of, if not all, assessments in a clinical setting, with a real patient and the opportunity for expedient feedback. Although nearly 90% of 201 athletic training programs reported assessing student capabilities on real patients in clinical practice, it has been reported that 70% performed fewer than half of their assessments in this manner.…”
Section: Benefits Of An Outcome-centric Educational Approachmentioning
confidence: 99%
“…[53][54][55][56][57] Further, both students and faculty believe that diverse clinical experiences and mentorship from practicing clinicians contribute to newly credentialed ATs feeling prepared to practice independently. 58,59 Given the perception from both educators and students of the learning potential in clinical education, it seems prudent to conduct the majority of, if not all, assessments in a clinical setting, with a real patient and the opportunity for expedient feedback. Although nearly 90% of 201 athletic training programs reported assessing student capabilities on real patients in clinical practice, it has been reported that 70% performed fewer than half of their assessments in this manner.…”
Section: Benefits Of An Outcome-centric Educational Approachmentioning
confidence: 99%